Exploring Halal Awareness and Its Impact on Skincare Purchase Intentions: A Structural Equation Modelling Approach - Vikaliana, Resista; Sukarno, Iwan; Raja Mohd Rasi, Raja Zuraidah (IKONOMIKA, 2024)
Indonesia, a nation with the highest number of Muslims, ranks second globally in terms of the consumption of halal cosmetics, following India. There is a growing worry about halal items. This study will examine the impact of halal awareness on intention to purchase skincare products. This study uses a Structural Equation Modelling technique using SMART PLS tools to analyze the factors driving purchase interest. These components include Religious beliefs, Self-identity, Halal Certification, and Halal Knowledge. The data collection in this study was conducted using a questionnaire, employing random sampling techniques to gather 57 samples. The findings of this study indicate that religion and self-identity do not substantially impact halal awareness. Conversely, the certification and understanding of halal practices substantially impact the awareness of halal products, including religious beliefs, self-identity, halal certification, and halal knowledge, which in turn has a major influence on the intention to acquire such products.